Krsna lifts up Mount Govardhana: Historical and comparative perspective - Ježić, Mislav (2014)
The myhic story of Krṣṇa's lifting up of Mount Govardhana is but one of numerous stories about his extraordinary feats. From the point of view of the history of religion it is a remarkable story that seems to imply the superiority of the new god Krṣṇa over Indra, Vedic king of the gods, and thus a change in the religious paradigm. Krṣṇa defies Indra by inviting the cowherds of Gokula not to celebrate Indra's festival after the rainy season, but instead to worship the mount Govardhana, their cows that graze upon it, and Krṣṇa himself. Indra grows furious and sends a terrible storm with thunder and lightning to destroy the cows and people of Gokula. In the midst of their suffering Krṣṇa raises the whole mountain with one hand and summons them to take shelter with their herds beneath it. He holds up the mountain for seven days until Indra desists seeing that he was not able to fulfill his threat, and saves the people and their cattle. Finally, Indra comes to the terms with Krṣṇa and calls him Upendra, his younger brother. Whoever compares this mythic story with the overall structure of the Balto-Slavic central mythic view of the permanent struggle between the heavenly god of thunder, heat and light Perunъ and the terrestrial and subterranean god of cattle and water Volosъ / Velesъ, will notice striking correlations. The correlations in content are strongly corroborated by Indo-European correspondences in expression as in all of the Purāṇic reports of this mythic story Indra is occasionally referred to as Parjanya, and once even as Valabhid. The tradition of this mythic story seems to have preserved the original names of the contenders: pre-Vedic Parjanya and Vala, corresponding to the Slavic Perunъ and Volosъ / Velesъ. A concise argumentation is offered to explain why Krṣṇa shares some features of the guardian of cows Vala and some of the dragonslayer Indra / Parjanya. In that respect he resembles the Slavic divinity Yarovit or Yarylo who shares the nature of his host Volosъ / Velesъ in the netherworld and of his father Perunъ in heaven. Therefore Krṣṇa does not seem to directly represent a younger form of Vala, but the story of his lifting of mount Govardhana does reflect, through an uninterrupted tradition which has left clear traces in the story formulae, the myth of the struggle between the two main divine contenders in the pre-Vedic myth of Indra / Parjanya and Vala, or the Balto-Slavic myth of Perunъ and Volosъ / Velesъ. The Govardhana mythic story provides ample material and a plastic description that likely surpasses anything found in the Balto-Slavic heritage. However, the results of the Balto-Slavic and Indo-European research of V. V. Ivanov, V. N. Toporov, and recently especially that of R. Katičić have attained such a degree of precision and clarity that they help in better understanding the meaning of this Indian Purāṇic mythic story and its importance which exceeds that what could have been guessed from the Indian material alone.
Projekt MZOS
ENG